The Development of Website-based Ngebel Tourism from an E-Government Perspective - Dian Suluh Kusuma Dewi; Jusuf Harsono; Desriyanti Desriyanti; Dwiana Binti Yulianti; Insyira Yusdiawan Azhar (Otoritas : Jurnal Ilmu Pemerintahan, 2022)
This article described the development of Ngebel tourism using a website. The tourism development concept uses the principles of e-government, such as government to citizens (G2C), government to government (G2G), and government to business (G2B). The study employed qualitative methods such as observation and focus group discussions (FGD) in collecting data. Data was analyzed using Nvivo 12 Plus software and the findings showed the Dolan Ngebel website applies the principles of government to citizens and government to business. This development was also received positively by the community and business people in the tourism industry. The website provides detailed information regarding the tourist attractions and facilities. Also, it is equipped with a map to make it easier for tourists to locate their destination. Overall, its use will help promote tourism to the locals and the international community. However, its development faces obstacles, including a lack of techsavvy human resources.